Overcoming the limitations to identify Dekkera bruxellensis in wine environment: performance and specificity evaluation of two species-specific RNA-FISH probes. - Branco, Patrícia (2019)
RNA-Fluorescence In Situ Hybridisation (RNA-FISH) allows the detection and identification of microorganisms in complex matrices in few hours being considered as one of the most powerful techniques for various applications in microbiology. Thus, it has the analytical potential for allowing specific detection of D. bruxellensis. However, some experimental difficulties can hamper its successful application such as: a) the autofluorescence of the sample and its interference with the RNA-FISH probe-conferred fluorescence, and b) the lack of probes with the desired levels of specificity and FISH performance. This is why this study was focused on overcoming the possible experimental drawbacks that can be found in RNA-FISH application for detecting D. bruxellensis in the wine environment and on evaluating the performance and specificity (both in silico and experimentally) of two RNA-FISH probes targeting to D. bruxellensis: a novel probe designed by us and a probe previously designed by other authors, 26S D. brux.5.1 .